Reflections of a rookie dean : lessons from the first year - Chandler, Prentice T. (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
Conversational in tone and providing highly practical advice for new deans, Reflections of a Rookie Dean: Lessons from the First Year chronicles the experiences of a novice college leader. Providing aspiring and new deans with insight and direction into the job of leading a college, this book is well positioned to help new leaders develop a better understanding of leadership in higher education and the challenges that new deans face. Deans, who function as middle managers in higher education, face a distinctive set of challenges. They are responsible for leading their college, implementing shared strategies, and motivating staff. But, they are also expected to enact the vision of senior leadership and mobilize support for broader institutional goals. To be successful, they must be skilled at managing both up and down the institutional hierarchy. This book provides insight into: * Understanding what effective leadership looks like in practice * Developing leaders in your college * Understanding how to initiate and implement change * Considering the ethical aspects of leading * Understanding how your leadership and college fits within the larger university * Strategically thinking about decision-making * Understanding the rhythms of serving as a new dean and leader This book is a must have for aspiring college leaders, organizers of leadership development programs, and university professors teaching coursework in higher education administration. Whether you are planning to be a college leader, are new to your role, or are looking to build capacity in your college, Reflections of a Rookie Dean can help you along your leadership journey.
Keywords: Chandler, Prentice T.; Deans (Education) -- United States.; Universities and colleges -- United States -- Administration.; Educational leadership -- United States.; Education -- Administration -- School Superintendents & Principals.; Educational administration and organization.; elektronické knihy; electronic books